USP13 regulates ferroptosis in chicken follicle granulosa cells by deubiquitinating ATG7 - Shunshun Han; Chunlin Yu; Mohan Qiu; Xia Xiong; Han Peng; Xiaoyan Song; Chenming Hu; Zengrong Zhang; Bo Xia; Li Yang; Jialei Chen; Shiliang Zhu; et al. (Poultry Science, 2024)
ABSTRACT: The development and maturation of follicles are intricately linked to egg production and reproductive performance of chickens. Granulosa cells death directly affects the development and maturation of follicles, thereby impacting the reproductive performance of hens. Ferroptosis is a new type of cell death, it is unknown how it affects the growth and development of chicken follicles. In this study, RNA-seq analysis revealed significant differences in the expression of ferroptosis-related genes between normal follicles and atretic follicles, suggesting a potential role for ferroptosis in follicle growth and development. In addition, we found that ubiquitin-specific protease 13 (USP13) was significantly upregulated in atrophic follicles. Overexpression of USP13 results in depletion of glutathione (GSH), peroxidation of lipids, accumulation of iron, and activation of ferroptosis in chicken granulosa cells. In contrast, USP13 knockdown significantly inhibited ferroptosis events. Mechanistically, USP13 prevents the degradation of autophagy related 7 (ATG7) by deubiquitinating it, thereby enhancing the stability of ATG7 protein and ultimately promoting ferroptosis. In conclusion, this study elucidates the crucial role of the USP13-ATG7 axis in regulating ferroptosis in chicken follicle granulosa cells, thereby presenting a novel avenue for molecular breeding research in chickens.